THE LACK OF INDIGENOUS CULTURAL KNOWLEDGE AND THE IMPAIRMENT OF NATIVE TITLE CLAIM ON ABORIGINAL CHILDREN AND IN THEIR LATER LIFE AS THE IMPACTS OF ASSIMILATION POLICY IN AUSTRALIA - Ayendi Ayendi (International Conference on Languages and Arts, 2014)
This paper discussed on the loss of indigenous cultural knowledge and the impairment of Aboriginal native title claim as the impacts of Assimilation policy on Aboriginal children in 1937 until 1970s and in their later life. This paper was an  areal study of Australia by using historical approach. This study belongs to qualitative reseach. The data were collected and analysed by using library research. The method of representing the results of the analysis or the finding was written descriptively. The findings revealed that the Assimilation policy by the Australian government considering it could give benefits to Aboriginal children at that time, in fact, on the other hand it brought the negative impacts causing them to lose their indigenous cultural knowledge such as the Aboriginal language,  characters, habits, skills and arts. The bad impacts did not only include those ones, they in the next generation lost their claim to the right on their native title lands.   Keywords: Assimilation policy, indigenous cultural knowledge, native title claim, and Aboriginal children